Colorblindness in Black and White: An Analysis of Core Tenets, Configurations, and Complexities. Issue 4 (October 2015) - Manning, Alex; Hartmann, Douglas; Gerteis, Joseph
The concept of colorblind racism has been developed in recent years to explain racial attitudes held by white Americans in the post–civil rights era. The authors use data from a new nationally representative survey with an oversample of black Americans to investigate the prevalence of core elements of colorblind ideology and to see the extent to which both black and white Americans adhere to three core dimensions of colorblindness theory: (1) abstract liberalism, (2) minimization of racism, and (3) cultural racism. They find that there are differences between black and white Americans with regard to their awareness of systemic dimensions of racial inequality. Yet they also find that the differences are not always large and that there is more awareness of racial inequality among whites than existing theories might suggest. Additionally, although blacks are much more likely than whites to reject some elements of colorblindness, the ideals of one element, abstract liberalism, are widely adopted by black and white Americans alike. The authors conclude with a discussion of the implications of these findings and the underlying tensions and variations for existing theories of colorblindness.